Biocompatible polymeric blend for pH driven delivery of cytarabine: Effect of feed contents on swelling and release kinetics. Issue 7 (31st January 2022) - Batool, Nighat; Sarfraz, Rai Muhammad; Mahmood, Asif; Zafar, Nadiah; Minhas, Muhammad Usman; Hussain, Zahid; Rehman, Umaira
Abstract: Purpose of this study was to prepare chitosan/tamarind crosslinked poly (methacrylic acid) hydrogels for pH responsive delivery of cytarabine by using aqueous free radical polymerization technique. Polymers were chemically cross‐linked with monomer (methacrylic acid) using methylene bisacrylamide as cross‐linking agent and ammonium per sulphate as a reaction initiator in aqueous medium. Developed hydrogels were characterized for morphology, physical existence, drug loading (%), compositional and structural analysis, thermal behavior and stability, drug release analysis (pH 1.2 and pH 7.4), and in vivo release kinetics. pH sensitive behavior was established by observing swelling and release behavior at different pH values (1.2 and 7.4). Biocompatibility of network was evaluated through acute oral toxicity studies in rabbits. Results revealed that cytarabine was efficiently loaded in prepared hydrogels with an entrapment efficiency of 54.67%–108.59%. Highest swelling ratio of 38.67 was noticed at pH 7.4. Maximum pH sensitive behavior was seen at pH 7.4 showing maximum drug release up to 94.51%. All developed formulations followed zero order release as confirmed from regression coefficient ( R 2  = 0.9912–0.9991). In‐vivo studies confirmed enhanced bioavailability of cytarabine. Histopathological examination and hemocompatibility studies proved that developed hydrogel system was safe, biocompatible, nonhemolytic in nature exhibiting no symptoms of dermal, ocular toxicities, and no changes in biochemical parameters of blood and histology of key organs. So, developed hydrogel system can be employed as an excellent drug delivery device where controlled drug delivery is desired. Abstract :